2022
DOI: 10.4236/ajps.2022.137065
|View full text |Cite
|
Sign up to set email alerts
|

Fungitoxicity of <i>Trichoderma longibrachiatum</i> (Rifai) Metabolites against <i>Fusarium oxysporum</i>, <i>Aspergillus niger</i> and <i>Aspergillus tamarii</i>

Abstract: An experiment was carried out to evaluate the fungitoxic effect of Trichoderma longibrachiatum (Rifai) metabolite on F. oxysporum, A. niger and A. tamarii. The fungi were collected from the International Institute of Tropical Agriculture (IITA) and Nigerian Institute of Science Laboratory Technology (NISLT). T. longibrachiatum was cultured on 1/4 strength Potato Dextrose Broth (PDB) following standard procedures. Its metabolite was extracted using 50 ml n-hexane with 50 ml Potato Dextrose Broth (PDB). The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The question of the resistance formation of uropathogenic Escherichia coli attracts many researchers. The resistance formation is ongoing as an adaptive mechanism, which continues to pose a risk to patients with UTIs [31,35]. Alternative ways to combat UPEC include the development and further theoretical application like vaccines, receptor analogs, pilicides and curlicides, bacterial interference, or phage therapy [31,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The question of the resistance formation of uropathogenic Escherichia coli attracts many researchers. The resistance formation is ongoing as an adaptive mechanism, which continues to pose a risk to patients with UTIs [31,35]. Alternative ways to combat UPEC include the development and further theoretical application like vaccines, receptor analogs, pilicides and curlicides, bacterial interference, or phage therapy [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…The resistance formation is ongoing as an adaptive mechanism, which continues to pose a risk to patients with UTIs [31,35]. Alternative ways to combat UPEC include the development and further theoretical application like vaccines, receptor analogs, pilicides and curlicides, bacterial interference, or phage therapy [31,33]. Perhaps the use of enzymes can also be added to this list.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imperfect fungi of the genus Trichoderma produce LO. A few studies have shown its antitumor [ 20 , 21 ] and antifungal [ 15 , 22 ] activities. Previously, our study demonstrated the effect of LO produced by the fungus Trichoderma harzianum Rifai on the process of biofilm formation in UPEC [ 23 ].…”
Section: Introductionmentioning
confidence: 99%